Treatment outcomes of pediatric acute myeloid leukemia: a retrospective analysis from 1996 to 2019 in Taiwan - Yung-Li Yang (Nature Portfolio, 2021)
Abstract Improvement in outcomes of children with acute myeloid leukemia (AML) is attributed to several refinements in clinical management. We evaluated treatment outcomes of Taiwanese pediatric AML patients in the past 20 years. Overall, 860 de novo AML patients aged 0–18 years and registered in the Childhood Cancer Foundation of R.O.C during January 1996–December 2019 were included. Survival analysis was performed to identify factors that improved treatment outcomes. Regardless of treatment modalities used, patients during 2008–2019 had better 5-year event-free survival (EFS) and overall survival (OS) rates than patients during 1996–2007. For patients received the TPOG-AML-97A treatment, only 5-year OS rates were significantly different between patients diagnosed before and after 2008. Patients with RUNX1–RUNX1T1 had similar relapse-free survival rates, but 5-year OS rates were better during 2008–2019. However, the survival of patients who received hematopoietic stem-cell transplantations (HSCT) did not differ significantly before and after 2008. For patients without relapse, the 5-year OS improved during 2008–2019. Non-relapse mortality decreased annually, and cumulative relapse rates were similar. In conclusion, 5-year EFS and OS rates improved during 2008–2019, though intensities of chemotherapy treatments were similar before and after 2008. Non-relapse mortality decreased gradually. Further treatment strategies including more intensive chemotherapy, novel agents’ use, identification of high-risk patients using genotyping and minimal residual disease, early intervention of HSCT, and antibiotic prophylaxis can be considered for future clinical protocol designs in Taiwan.